Normalização das teses e dissertações no contexto da Biblioteca Digital - Moura, Eliene Maria Vieira de (2009)
The Biblioteca Digital de Teses e Dissertações (BDTD) has provided greater visibility and agility in the process of publishing thesis and dissertations. Thus, the way of publishing thesis and dissertations require a series of cautions from the responsible institutions, among which the scientific standardization quality. The general aim of this study was to analyze the standardization state of thesis and dissertations available at the Universidade Federal do Ceará (UFC) BDTD in order to suggest possible solutions aiming to improve the standardization quality of such works. For doing so, it was also considered the use of standardization services offered by UFC. As a theoretical basis we used reference books on scientific communication, digital libraries and standardization reports decrees of UFC, Fundação Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), Instituto Brasileiro de Informação em Ciência e Tecnologia (IBICT), among others. We decided for accomplishing a descriptive research divided into two stages: the first one used the quantitative approach. It dealt with the standardization of thesis and dissertation analysis published in the DLTD/UFC according to the ABNT and IBGE standards, using an evaluation tool composed by variables which represent the demanding of such standards. On the second stage we tried to find out, through the use of a questionnaire, directed to the authors and advisors, the factors which took the thesis and dissertations to the level of standardization presented previously. This stage approaches the data quantitative as well as qualitatively. The conclusions show that the DLTD/UFC thesis and dissertations present standardization faults and suggest that such faults have been motivated by indefinition of standards that must be used and that it doesn’t occur due to non-acquaintance with support service to academic work standardization. It remained clear that there is not, on behalf of the post graduation programs of UFC, a real consistence of visibility implications provided by the DLTD to the works they have available to the public.